Identification of Disease-associated Traits and Clonotypes in the T Cell Receptor Repertoire of Monozygotic Twins Affected by Inflammatory Bowel Diseases - Rosati, Elisa; Pogorelyy, Mikhail V; Dowds, C Marie; Moller, Frederik T; Sorensen, Signe B; Lebedev, Yuri B; Frey, Norbert; Schreiber, Stefan; Spehlmann, Martina E; Andersen, Vibeke; Mamedov, Ilgar Z; Franke, Andre (Journal of Crohn's & colitis, 2020)
BACKGROUND AND AIMS: Intestinal inflammation in inflammatory bowel diseases [IBD] is thought to be T cell mediated and therefore dependent on the interaction between the T cell receptor [TCR] and human leukocyte antigen [HLA] proteins expressed on antigen presenting cells. The collection of all TCRs in one individual, known as the TCR repertoire, is characterised by enormous diversity and inter-individual variability. It was shown that healthy monozygotic [MZ] twins are more similar in their TCR repertoire than unrelated individuals. Therefore MZ twins, concordant or discordant for IBD, may be useful to identify disease-related and non-genetic factors in the TCR repertoire which could potentially be used as disease biomarkers. METHODS: Employing unique molecular barcoding that can distinguish between polymerase chain reaction [PCR] artefacts and true sequence variation, we performed deep TCRα and TCRβ repertoire profiling of the peripheral blood of 28 MZ twin pairs from Denmark and Germany, 24 of whom were discordant and four concordant for IBD. RESULTS: We observed disease- and smoking-associated traits such as sharing, diversity and abundance of specific clonotypes in the TCR repertoire of IBD patients, and particularly in patients with active disease, compared with their healthy twins. CONCLUSIONS: Our findings identified TCR repertoire features specific for smokers and IBD patients, particularly when signs of disease activity were present. These findings are a first step towards the application of TCR repertoire analyses as a valuable tool to characterise inflammatory bowel diseases and to identify potential biomarkers and true disease causes.
Keywords: ulcerózní kolitida; leukocytární L1-antigenní komplex; Crohn Disease; Denmark; Feces; geny TcR beta; Male; Genes, T-Cell Receptor alpha; dvojčata monozygotní; receptory antigenů T-buněk alfa-beta; Sequence Analysis, DNA; monozygotic twins; sekvenční analýza DNA; Crohnova nemoc; Adult; C-reaktivní protein; dospělí; mužské pohlaví; Leukocyte L1 Antigen Complex; Dánsko; Smoking; posouzení stavu pacienta; Germany; geny TcR alfa; lidé; Genes, T-Cell Receptor beta; Patient Acuity; ženské pohlaví; Humans; Německo; Colitis, Ulcerative; Twins, Monozygotic; inflammatory bowel diseases [IBD]; C-Reactive Protein; Female; feces; kouření; Receptors, Antigen, T-Cell, alpha-beta; T cell receptor [TCR] repertoire